A modified bacterial foraging algorithm based optimal reactive power dispatch - Palvai Lokender Reddy; G. Yesuratnam (Institute of Advanced Engineering and Science, 2019)
This article describes an approach for optimal reactive power dispatch problem using a Modified Bacterial Foraging Algorithm. Modified bacterial foraging algorithm introduces a differential evolution operator in chemotaxis to overcome tumble failure in tumble step and accelerates the convergence speed of the original operator. In the new algorithm chaotic dynamics are used to generate initial population to have uniform distribution. The proposed new algorithm is applied to Optimal reactive power dispatch problem with two objective functions; minimization of real power loss and voltage stability L-index. The objective functions are minimized by optimally choosing the control variables such as generator excitations, tap positions of on-load tap changing transformers and switched var compensators. The proposed approach has been evaluated on an IEEE 30 bus standard test system. The performance of the proposed algorithm is compared with other evolutionary computation algorithms in the literature and the effectiveness of the proposed algorithm is demonstrated.